2019
DOI: 10.1108/ijpdlm-08-2018-0306
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain technologies, interorganizational network and firm performance

Abstract: Purpose Supply chain management literature recognizes that interorganizational networks provide resources that convey critical benefits, such as capital, competitive advantage and efficient strategy implementation. The purpose of this paper is to leverage network theory and identify technological innovations as the antecedents for organizations to achieve stronger interorganizational networks. Specifically, this paper investigates how supply chain technologies of its logistics affiliate, Cainiao Network (CN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…These practical benefits can be verified with the promotion of recycling chain integration, which in turn enhances network robustness. This finding corroborates the ideas ofFalcone et al (2019) who suggested that multiplexity collaboration can enhance trust and commitment among the network partners. Thus, we propose: Proposition 4.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These practical benefits can be verified with the promotion of recycling chain integration, which in turn enhances network robustness. This finding corroborates the ideas ofFalcone et al (2019) who suggested that multiplexity collaboration can enhance trust and commitment among the network partners. Thus, we propose: Proposition 4.…”
supporting
confidence: 91%
“…‘Receptivity’ represents the ability to capture these potential network values across organisational boundaries. Falcone et al (2019) referenced a case study of Alibaba Group and Cainiao, which proposed that innovative technologies are the preconditions for achieving 3Rs within the organisation based on Gulati et al's (2011) study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They had a first‐mover advantage and were often equipped with the latest technology and technical expertise in logistics. For example, through Big Data technology and collaboration with various delivery partners, Cainiao Network successfully developed a smart logistics system across China (Falcone, Kent, & Fugate, 2020). Cainiao's successful use of automation, algorithms, and digital networks suggests that it is worth examining the possibility of further resource recovery and optimization in the context of online shopping.…”
Section: Reverse Logistics and Online Shoppingmentioning
confidence: 99%
“…Alibaba Group is a Chinese e-commerce corporation with the largest online shopping platform and the initiators of such a new business model. In this business model consumers buy goods on Taobao (a C2C and B2C e-commerce platform) and transfer their money through Alipay which is similar to PayPal in the United States and European eCommerce (Falcone et al, 2019). Alipay is a virtual pay-ment platform launched in 2004 by the Alibaba Group that serves as a payment middleman between e-sellers and the customers, solving the long-term trust issue (Lu, 2018).…”
Section: W-o Strategiesmentioning
confidence: 99%